Death to the Constitution! Restoration, royalism and anti-liberalism in the Spanish Atlantic (1820 1833). Coordinated by Álvaro París. Presentation - París, Álvaro (Hispania Nova, 2022)
On the bicentenary of the second absolutist restoration of Ferdinand VII (1823-1833), this special issue aims to shed a new light on one of the most obscures periods of Spanish recent history. To this end, it approaches the reaction against liberalism from a comparative and transatlantic perspective, through a dialogue between peninsular Spain and Spanish America. The authors address issues such as the divisions within the royalist camp, the plebeian dimension of anti-liberalism, the counterrevolutionary readings of the independence of Spanish America or the motivations of the royalist fighters. Taken as a whole, these six papers provide a vantage point for rethinking a period as full of prejudices as challenging for research.